Respuestas

2012-12-01T23:40:20+01:00

A) primero simplificamos

(x-3)(x+3)-(x-3) =

x^2-9-x+3 =

x^2-x-6 

ahora utilizamos la formula general

te la escribo

-b+-(la raiz cuadrada de)b^-4ac/2a

sustituyendo

-(1)+- (la raiz cuadrada de)(-1)^2 -4(1)(-6)/2 =

1+-(la raiz cuadrada de)25/2 =

x1 = 1+ 5/2 = 3

x2 = 1- 5/2 = 2

entonces A) x1 = 3   x2 = 2

B)

(1/2x-2x^3)(1/2x-2x^3) =

(1/4x^3-2x^4+4x6)(1/2x-2x3) =

-8x^9+6x^7-1/2x^6-1x5+1/8x^4

c)

(2/3x-1/2X^2)^2 =

 (2/3x-1/2X^2)(2/3x-1/2X^2) =

4/9x^2-1/3x^3-1/3x^3+1/4x^4 =

1/4x^4-2/3x^3+4/9x2